PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS BUDAYA UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA PADA SISWA SEKOLAH DASAR - KURNIAWAN, ANTOK (Jurnal Pendidikan Dasar, 2025)
This study aims to develop an interactive e-module based on local culture as a mathematics learning media to enhance elementary school students’ conceptual understanding. The research applied the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The study involved 28 fourth-grade students from an elementary school in Bungo as participants. Validation by content and media experts indicated that the e-module is highly feasible for use. Field trials showed that the e-module not only increased students’ interest in mathematics but also facilitated their conceptual understanding, as the material was presented within a familiar cultural context. The average score of students’ conceptual understanding improved from 64.2 in the pre-test to 85.3 in the post-test